Profitability & Leverage as Determinants of The Price to Book Value of Companies Listed on Jakarta Islamic Index - Muhammad Iqbal; Reny Fitriana Kaban; Henny Ritha (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
A steady increase in the stock market price reflects the maximization of corporate value. The Price to Book Value ratio serves as a metric for assessing the growth in a company's value. Profitability and leverage policies are just two of the several aspects that influence the company's overall value. This study aims to evaluate the impact of financial ratios, specifically profitability as measured by Return on Equity and leverage indicated by the Debt to Equity Ratio, on the Price to Book Value of companies listed on the Jakarta Islamic Index between 2018 and 2023, during which time the Covid 19 Pandemic occurred. This study distinguishes itself from previous research through its methodological approach. The research utilized a descriptive and quantitative methodology. Additionally, the sample for this study was selected using a purposive sampling with eleven firms that are consistently listed on the Jakarta Islamic Index for the timeframe 2018-2023. This research employs panel data regression as its analytical approach. The findings from the statistical tests reveal that the Profitability Ratio significantly affects the Price to Book Value, whereas the Leverage Ratio does not exhibit a notable impact. This suggests that while Profitability plays a crucial role, Leverage does not. It is recommended that Issuers consistently strive to sustain or enhance profitability under all circumstances, which would contribute to an increase in the company's overall value to face unexpected events such as Covid 19, businesses must examine both capital and debt financing to maintain the trust of shareholders and other stakeholders.